2020
DOI: 10.1158/1055-9965.epi-19-0710
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blocker Use and Lung Cancer Mortality in a Nationwide Cohort Study of Patients with Primary Non–Small Cell Lung Cancer

Abstract: Background: b-Adrenergic receptor blockers have been associated with improved survival among patients with different types of malignancies, but available data for patients with nonsmall cell lung cancer (NSCLC) are contradictory and limited to small hospital-based studies. We therefore aimed to investigate whether b-blocker use at the time of cancer diagnosis is associated with lung cancer mortality in the largest general population-based cohort of patients with NSCLC to date.Methods: For this retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…This tool evaluated four methodological components: reporting, external validity, internal validity (bias and confounding), and power. Only two studies, in the reporting [ 35 , 49 ] and external validity [ 36 , 41 ], achieved the maximum score (11 and 3, respectively). No study reached the maximum score in internal validity (bias and selection bias) and power items.…”
Section: Resultsmentioning
confidence: 99%
“…This tool evaluated four methodological components: reporting, external validity, internal validity (bias and confounding), and power. Only two studies, in the reporting [ 35 , 49 ] and external validity [ 36 , 41 ], achieved the maximum score (11 and 3, respectively). No study reached the maximum score in internal validity (bias and selection bias) and power items.…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous retrospective studies that evaluated the impact of BB use on clinical outcome in patients with NSCLC. Some of these population-based cohort studies showed no association between BB use and reduced mortality among lung cancer patients [ 98 , 99 , 100 ]. However, others indicated that BB use was indeed associated with an improved outcome because BB use during chemotherapy treatment improved OS in patients with metastatic NSCLC [ 101 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Lung cancer is one of the most prevalent cancer type worldwide along with more than 1.7 million of deaths annually among cancer-related mortalities (1)(2)(3). The prognosis of lung cancer is still not at the desired point despite the advanced therapeutic strategies such as tumorectomy, chemo-/radio-therapy, immune therapy, etc.…”
Section: Introductionmentioning
confidence: 99%